Error assessment in post-necking strain hardening behaviour identification of mild steel sheet. Issue 3 (August 2016) - Coppieters, S.; Hakoyama, T.; Denys, K.; Debruyne, D.; Kuwabara, T.
Abstract: The information hidden in the diffuse neck of a tensile test on a thin metal sheet can be extracted using a special case of the non-linear virtual fields method yielding the so-called post-necking strain hardening behaviour. The method, however, requires a number of assumptions which are scrutinized in this paper. To eliminate experimental errors which could potentially hamper the assessment, virtual test data (i.e. strain fields at different load steps) is generated using a FE model of the tensile test. The identification strategy is then used to retrieve the reference strain hardening behaviour used in the FE simulation. This approach is used to study the necessity of incorporating rate-dependent plasticity in the identification procedure. Additionally, the necessary plane stress condition in the diffuse neck is studied.